‘Advertising’ day-to-day life: a communication approach to culture as a crossroads - San Nicolás Romera, César (COMMUNICATION. International Journal of Audiovisual Communication, Advertising and Cultural Studies, 2022)
In this paper, we are trying to analyze transformations that current communication settings are submitted to as public channels of sociocultural activity of the people. This fact implies the examination of changes experienced by social paradigm changes and its conversion into a narrative line that uses the cultural dimension as a claim. The ability of mass media to make public the reality gets involved with the Advertising power in order to turn themselves into organizers of the society activity.